Challenges, opportunities and priorities for transitioning to low emissions agriculture - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
"Challenges, opportunities and priorities for transitioning to low emissions agriculture" was presented by Lini Wollenberg at a NUI Galway seminar on January 30, 2020.